The stability of the MEMS 2D mirror’s operating point in terms of eye tracking systems - Pomianek, Mateusz; Piszczek, Marek; Maciejewski, Marcin; Krukowski, Piotr (Photonics Letters of Poland, 2020)
This paper describes research on the stability of the MEMS mirror for use in eye tracking systems. MEMS mirrors are the main element in scanning methods (which is one of the methods of eye tracking). Due to changes in the mirror pitch, the system can scan the area of the eye with a laser and collect the signal reflected. However, this method works on the assumption that the inclinations are constant in each period. The instability of this causes errors. The aim of this work is to examine the error level caused by pitch instability at different points of work. Full Text: PDF References W. Fuhl, M. Tonsen, A. Bulling, and E. Kasneci, "Pupil detection for head-mounted eye tracking in the wild: an evaluation of the state of the art," Mach. Vis. Appl., vol. 27, no. 8, pp. 1275-1288, 2016, CrossRef X. Wang, S. Koch, K. Holmqvist, and M. Alexa, "Tracking the gaze on objects in 3D," ACM Trans. Graph., vol. 37, no. 6, pp. 1-18, Dec. 2018 CrossRef X. Xiong and H. Xie, "MEMS dual-mode electrostatically actuated micromirror," Proc. 2014 Zo. 1 Conf. Am. Soc. Eng. Educ. - "Engineering Educ. Ind. Involv. Interdiscip. Trends", ASEE Zo. 1 2014, no. Dmd, 2014 CrossRef E. Pengwang, K. Rabenorosoa, M. Rakotondrabe, and N. Andreff, "Scanning micromirror platform based on MEMS technology for medical application," Micromachines, vol. 7, no. 2, 2016 CrossRef J. P. Giannini, A. G. York, and H. Shroff, "Anticipating, measuring, and minimizing MEMS mirror scan error to improve laser scanning microscopy’s speed and accuracy," PLoS One, vol. 12, no. 10, pp. 1-14, 2017 CrossRef C. Hennessey, B. Noureddin, and P. Lawrence, "A single camera eye-gaze tracking system with free head motion," Eye Track. Res. Appl. Symp., vol. 2005, no. March, pp. 87-94, 2005 CrossRef C. H. Morimoto and M. R. M. Mimica, "Eye gaze tracking techniques for interactive applications," Comput. Vis. Image Underst., vol. 98, no. 1, pp. 4-24, Apr. 2005 CrossRef S. T. S. Holmström, U. Baran, and H. Urey, "MEMS laser scanners: A review," J. Microelectromechanical Syst., vol. 23, no. 2, pp. 259-275, 2014 CrossRef C. W. Cho, "Gaze Detection by Wearable Eye-Tracking and NIR LED-Based Head-Tracking Device Based on SVR," ETRI J., vol. 34, no. 4, pp. 542-552, Aug. 2012 CrossRef T. Santini, W. Fuhl, and E. Kasneci, "PuRe: Robust pupil detection for real-time pervasive eye tracking," Comput. Vis. Image Underst., vol. 170, pp. 40-50, May 2018 CrossRef O. Solgaard, A. A. Godil, R. T. Howe, L. P. Lee, Y. A. Peter, and H. Zappe, "Optical MEMS: From micromirrors to complex systems," J. Microelectromechanical Syst., vol. 23, no. 3, pp. 517-538, 2014 CrossRef J. Wang, G. Zhang, and Z. You, "UKF-based MEMS micromirror angle estimation for LiDAR," J. Micromechanics Microengineering, vol. 29, no. 3, 201 CrossRef